2018
DOI: 10.1088/1361-6641/aadc00
|View full text |Cite
|
Sign up to set email alerts
|

Reduced thermal conductivity of a Ge1−xSnxlayer formed on a self-assembled Sn nanodot template

Abstract: Self-assembled Sn nanodots were formed on SiO 2 and the crystallinity and Sn composition of a Ge 1−x Sn x polycrystal formed on the Sn nanodots were evaluated. The average diameter of the Sn nanodots was 17.1 nm, and their density was 1.5×10 9 cm −2 . Raman spectroscopy revealed that the crystallinity of Ge 1−x Sn x increased from 52.29% to 86.82% as the Ge deposition temperature increased from 100 °C to 225 °C. However, agglomeration degraded the surface roughness when the Ge deposition temperature was high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Still, the thermal properties of GeSn alloys have not been explored yet, and their potential as CMOS-integrable TE materials remains unknown. The few existing experimental reports deal with amorphous or polycrystalline films, , while, ideally, good thermoelectric materials should be crystalline, where phonon scattering occurs without disrupting the electrical conductivity …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Still, the thermal properties of GeSn alloys have not been explored yet, and their potential as CMOS-integrable TE materials remains unknown. The few existing experimental reports deal with amorphous or polycrystalline films, , while, ideally, good thermoelectric materials should be crystalline, where phonon scattering occurs without disrupting the electrical conductivity …”
Section: Introductionmentioning
confidence: 99%
“…15 These successes were enabled by the progress made in the GeSn epitaxy on Ge/Si substrates 16,17 as CMOS-integrable TE materials remains unknown. The few existing experimental reports deal with amorphous or polycrystalline films, 18,19 while, ideally, good thermoelectric materials should be crystalline, where phonon scattering occurs without disrupting the electrical conductivity. 20 In this work, the TE properties of high-quality GeSn epitaxial layers on Si are investigated.…”
Section: ■ Introductionmentioning
confidence: 99%
“…For instance, Tenanodots in ZnO/BTS interfaces, enhanced σ and S due to the quantum confinement effect, 70 Ge-nanodots in Sibased material reduced κ t to ~1.2 Wm −1 K −1 , 71 Aunanodots in Bi 2 Te 3 nanocomposites reduced κ lat to ~0.47 Wm −1 K −1 , 72 and Sn-nanodots in Ge reduced κ t to 2.305 Wm −1 K −1 . 73 Likewise, nanowires with small electron effective mass and a diameter greater than 5 nm could attain low κ t as well as high PF, 69 whereas, superlattices enhance the performance of TE materials by reducing the κ t by controlling the transport of phonons and electrons without any effect on PF. 33 For instance, Subramanian et al showed that the multiple-quantumwell of Bi 2 Te 3 -Sb 2 Te 3 superlattices provide a high ZT value of ~2.4 by reducing κ t .…”
Section: Low-dimensional (D) Materialsmentioning
confidence: 99%
“…This study focused especially on reducing the thermal conductivity by the enhancement of phonon scattering. [8][9][10][11] Polycrystalline materials with a grain size larger than the mean free path of an electron and smaller than that of a phonon are effective in reducing the thermal conductivity. Therefore, poly-Si is expected to be a thermoelectric material.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the thermal conductivity of polycrystalline Si 1−x Ge x can be further reduced by introducing Sn atoms, whose mass is 4.2 times greater than that of Si and 1.6 times greater than that of Ge, into the lattice substitution positions. 9,10) Similar to the introduction of Ge into Si, it is theoretically predicted that the substitution of Sn atoms into Si 1−x Ge x will result in lower thermal conductivity compared to Si 1−x Ge x . 18) This theoretical calculation shows that the introduction of Sn as well as a certain high Si content is necessary to reduce the thermal conductivity practically as the solid solubility limits of Sn in Ge and Si are very low.…”
Section: Introductionmentioning
confidence: 99%